1998
DOI: 10.1063/1.366865
|View full text |Cite
|
Sign up to set email alerts
|

A Mössbauer spectral study of Nd6Fe13X, where X is Cu, Ag, and Au and of the spin reorientation in Nd6Fe13Si

Abstract: The Mössbauer spectra of Nd6Fe13X, where X is Si, Cu, Ag, and Au, have been measured between 80 and 500 K. A model corresponding to a basal alignment of the magnetic moments leads to excellent, internally consistent, fits for the Cu, Ag, and Au compounds. The resulting temperature dependences of the spectral hyperfine parameters are uniform and reveal for each Fe site the expected correlations between the isomer shift and the Wigner–Seitz cell volume and the hyperfine field and the number of Fe near neighbors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
24
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 20 publications
11
24
0
Order By: Relevance
“…After correction, the latter Fe1 moments are in good agreement with those found for Pr Fe Sn and Nd Fe Sn in the course of the present investigation. Also, there is much better agreement with the large hyper"ne "elds reported in MoK ssbauer investigations for this Fe site [13,14].…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…After correction, the latter Fe1 moments are in good agreement with those found for Pr Fe Sn and Nd Fe Sn in the course of the present investigation. Also, there is much better agreement with the large hyper"ne "elds reported in MoK ssbauer investigations for this Fe site [13,14].…”
Section: Discussionsupporting
confidence: 77%
“…It is also consistent with a model description proposed in Ref. [14] in which the magnetic anisotropy of several Nd Fe X compounds is taken to depend strongly on the mixing of the Nd valence electron states with the valence electron states of the X atoms, which is very sensitive to the electronic con"guration of X. In this model description, the compounds Nd Fe Au and Nd Fe Sn fall into the categories basal plane type anisotropy and uniaxial anisotropy, respectively.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In several investigations it was found that magnetic ordering is characterized by a Néel-type transition at temperatures around 400 K [9][10][11][12] which was also confirmed by Mössbauer spectroscopy [7,10]. The absence of a spontaneous magnetization of any significance at 4.2 K suggests that the magnetic structure consists of an antiferromagnetically ordered rare earth sublattice and an antiferromagnetically ordered Fe sublattice [9,11].…”
Section: Introductionmentioning
confidence: 87%
“…There are two rare earth sites, R 1 (8f) and R 2 (16l) and four Fe sites, Fe 1 (4d), Fe 2 (16k), Fe 3 (16l 1 ) and Fe 4 (16l 2 ). The magnetic properties of the R 6 Fe 13 X compounds were studied by numerous authors [2,[4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%